Culturally Responsive Science Instruction and Preservice Teachers’ Affiliation Motivation - Aisyah Ali; Akhmad Kadir; Kusdianto Kusdianto (Academia Open, 2025)
General Background: Teacher education in multicultural settings like Papua demands pedagogies that integrate cultural, linguistic, and communal values to foster inclusive learning. Specific Background: Culturally Responsive Science Instruction (PRB) operationalizes Culturally Responsive Teaching through the Hem Re Yegokhe practice, embedding local Indigenous knowledge into science instruction. Knowledge Gap: While prior research highlights cognitive benefits of culturally responsive pedagogy, the socio-affective dimension, particularly affiliation motivation among preservice teachers in frontier Indonesian regions, remains underexplored. Aims: This study investigates the effects of PRB on preservice teachers’ affiliation motivation and examines the mediating role of Cultural Exploration Experience (PEB). Results: Using a pretest–posttest design with 173 participants and structural equation modeling, PRB significantly enhanced PEB (β = 0.681, p < .001) and affiliation motivation (β = 0.436, p = .018), with PEB providing a significant partial mediation (β_indirect = 0.130, p = .025). Novelty: By situating culturally grounded science instruction within a Papuan context, this study integrates Self-Determination Theory and culturally sustaining pedagogy to reveal affective mechanisms underlying multicultural teacher education. Implications: Findings urge teacher-training institutes to embed local cultural practices into curricula, strengthening social cohesion and motivational readiness of preservice teachers in diverse and underdeveloped regions. Highlights: PRB significantly boosts preservice teachers’ cultural exploration and social motivation. Cultural exploration experience acts as a partial mediator between PRB and affiliation motivation. Embedding local practices like Hem Re Yegokhe enhances multicultural teacher education impact. Keywords: Culturally Responsive Instruction, Affiliation Motivation, Cultural Exploration, Teacher Education